ANALYSE SPRECHAKTE AUF DEM DIALOG TEXT IM KONTAKTE DEUTSCH 1 - YULIAWATI, SITI (LATERNE, 2013)
An important role of a language is a tool of communication between living creatures. People need language in daily life to be able to run the activities of his life. At the time a person wants to send a message, he would say through a speech. And when someone wants to deliver a speech, he not only produce utterances but also shows the actions through speech-ments of these. The actions displayed by speech called speech acts. This study discusses the types of speech acts consist of locutionary act and illocutionary act. The purpose of this study was to describe the type of locution and illocutionary speech acts in dialogue text in the Kontakte Deutsch 1. In this study, researchers used the theory of Searle who classify illocutionary acts into five, namely assertive, directive, commissive, expressive, and declarative. Subject of this study is the dialogue texts exist in Deutsch 1 Kontakte while the study object is the speech act. The method used in this analysis is descriptive qualitative method because the results of data processing are presented with words instead of numbers. Data collection in this study was done by using libraries. The research results are as follows: (1) type of speech locutionary act found in text dialog in the Kontakte Deutsch 1 are declarative and interrogative. (2) The type of illocutionary act found in text dialog in the Kontakte Deutsch 1 are assertive, directive, and expressive. Keywords: speech acts, dialogue text, locutioary akt, ilocutionary akt